Did Donald Trump's presidency reshape Americans' prejudices?. Issue 3 (March 2023) - Ruisch, Benjamin C.; Ferguson, Melissa J.
Abstract: Did the presidency of Donald Trump affect Americans' intergroup attitudes? Converging evidence from recent experimental and longitudinal studies suggests that Trump's political rise led his supporters to increase their reported prejudice toward traditionally minoritized racial and religious groups in the USA.